Kepemimpinan Stratejik dalam Mempengaruhi Kinerja Karyawan Melalui Kepuasan Kerja sebagai Variabel Mediasi pada Divisi Pengadaan Umum dan Jasa Fasilitas PT. Dirgantara Indonesia (Persero) - Uus Mulyana; Ade Sobandi; Budi Santoso (Business Education Program of Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to obtain the results of a study and analysis regarding the influence of strategic leadership on employee performance with job satisfaction as mediation in the General Procurement and Facility Services Division of PT. Dirgantara Indonesia (Persero) which is located in the city of Bandung. The population in this study are all employees who are members of the General Procurement and Facility Services Division of PT. Dirgantara Indonesia (Persero), totaling 84 employees who have become respondents in this study. This research method uses a quantitative approach method, as well as a method of collecting data through questionnaires which are distributed to all employees using the Google Form media. The hypothesis testing technique in this study uses structural equation modeling / SEM techniques using AMOS software. The results of this study indicate that the first hypothesis of strategic leadership can have a positive effect, but not significantly on employee performance. The second hypothesis shows that strategic leadership can have a positive and significant effect on employee job satisfaction. The third hypothesis explains that employee job satisfaction has a negative and not significant effect on employee performance. Furthermore, the last hypothesis reveals that employee job satisfaction cannot mediate the effect of strategic leadership on employee performance. Keywords: Strategic Leadership, Job Satisfaction, Employee Performance, PT. Indonesian Aerospace.